Experimental Study of the Effect of Addition Glass Wool as Insulation Material on the Performance of Flat Plate Type Solar Collectors - Rachmanita, Risse Entikaria; Syafi'i, Moh. Yusuf; Ahmadi, Haerul (Journal of Renewable Energy and Mechanics, 2022)
Clean energy sources are becoming more and more common, and the use of solar thermal energy is also increasing. Indonesia gets sunlight all year round with a radiation radiation of 4.80 kWh/m2. The potential of solar energy can be utilized by converting solar radiation into new energy. The flat plate solar water collector is a simple solar energy conversion system for hot water production. This study aims to determine the amount of heat energy received by the solar collector, determine the temperature of the water that comes out (Tout) on the solar collector and determine the thermal efficiency (η) on the flat plate solar collector with the addition of glass wool as an insulation material. The results showed that the highest thermal energy that enters the solar collector is 832.58 W and produces an output water temperature of 320.7 K or 47.7 °C. The efficiency that can be achieved by the solar collector is quite efficient, which is 47.92%.